(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Nowadays, there is a growing interest in the use of interactive methods, innovative technologies, pedagogical technologies in education, one of the reasons for which to date students are taught only ready-made knowledge, and the use of modern technologies requires them to think independently, teaches to search, analyze and draw conclusions.